2017
DOI: 10.1099/jmm.0.000397
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated quinolone resistance determinants among Gram-negative bacteraemia isolates: a hidden threat

Abstract: PMQRs compromised the bactericidal activity of ciprofloxacin and levofloxacin when expressed in Enterobactercloacae, S. maltophilia or Klebsiellapneumoniae and when more than one co-existed. PMQR determinants represent an unrecognized threat, capable to compromise the in vitro activity of quinolones if expressed in a favourable genetic environment and to favour selection of resistant mutants by widening the mutant selection window of these agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Plasmid-mediated quinolone resistance has been shown to compromise the bactericidal activity of fluoroquinolones when expressed in Enterobacteriaceae [72]. For example, plasmidic transfer of genes has resulted in spread of resistant strains among E. coli , K. pneumoniae , and Proteus species [73].…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid-mediated quinolone resistance has been shown to compromise the bactericidal activity of fluoroquinolones when expressed in Enterobacteriaceae [72]. For example, plasmidic transfer of genes has resulted in spread of resistant strains among E. coli , K. pneumoniae , and Proteus species [73].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance is attributed to plasmids as a source of the resistant genes [12] and can be categorized based on of prevalence of antimicrobial resistance genes as extended-spectrum β-lactamase (ESBLs) [13], plasmid-mediated quinolone resistance (PMQR) genes [14] especially involving Qnr proteins and the aminoglycoside acetyltransferase variant determinant (AAC(6')-Ib-cr), which has emerged and is now described worldwide [15] and 16S rRNA methylase (16S-RMTase)…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Moreover, although inoculum size effects for levofloxacin, amikacin, and carbapenems were apparent for some isolates in our study, the inoculum size effects for levofloxacin and amikacin were not significant in the conjugation experiments. Margaritis et al have reported that half of the transconjugants of PMQRs (2/4 strains) showed inoculum size effects for levofloxacin (1-, 2-, 4-, and 16-fold: MIC of 10 7 CFU/mL per MIC of 10 5 CFU/mL) (9). However, they also showed that the inoculum size effects for quinolone were significant for laboratory strains which did not harbor acquired quinolone resistance genes.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the inoculum size effect for the action of quinolone on bacteria expressing PMQR genes has also been described (9,13). However, in one of these studies, it was reported that only half of the transconjugants of PMQRs (2/4 strains) showed an inoculum size effect for quinolone (9). There has been no study describing the inoculum size effect for strains expressing both MBL and PMQRs.…”
Section: Introductionmentioning
confidence: 99%